Pengaruh Tingkat Pendidikan Terhadap Pertumbuhan Ekonomi di Kota Gorontalo - Husen Arifin; Raflin Hinelo; Agil Bahsoan; Radia Hafid; Sudirman Sudirman (State University of Gorontalo, 2023)
The data used is secondary data obtained from the Gorontalo City BPS (Central Bureau of Statistics for the City of Gorontalo) using Documentation analysis techniques. On the results of the correlation coefficient test, the person correlation coefficient value was 0.323. This shows that there is a low relationship between the level of education (X) and economic growth (Y). The test results for the coefficient of determination obtained an R-Square value of 0.104. this value means that 10.4% of the variability regarding economic growth in Gorontalo City can be explained by the level of education. While the remaining 89.6% is influenced by other variables not examined in this study. Furthermore, for the results of the t test it is known that the t value is 1.080 t table 2.178 and the significance level is 0.306 0.00, thus the research hypothesis which states that there is an influence between the level of education on economic growth in the city of Gorontalo, is rejected in this study.